Slavery, Agriculture, and Malaria in the Arabian Peninsula - Reilly, Benjamin (Ohio University Press, 2015)
This book illuminates a previously unstudied phenomenon: the large-scale employment of people of African ancestry as slaves in agricultural oases within the Arabian Peninsula. The key to understanding this unusual system is the prevalence of malaria within Arabian Peninsula oases and drainage basins, which rendered agricultural lands in Arabia extremely unhealthy for people without genetic or acquired resistance to malarial fevers. In this way, Arabian slave agriculture had unexpected similarities to slavery as practiced in the Caribbean and Brazil. This book synthesizes a body of historical and ethnographic data about slave-based agriculture in the Arabian Peninsula. Reilly uses an innovative methodology to analyze the limited historical record and a multidisciplinary approach to complicate our understandings of the nature of work in an area that is popularly thought of solely as desert.
Description based on print version record.
KU Select 2018: HSS Backlist Books
Keywords: History / World; History; Electronic books